Prevalence and characteristics of HIV/HBV and HIV/HCV coinfections in Tuscany - Puglia,Monia (2016)
Abstract Introduction Worldwide about 30% of HIV-infected patients are coinfected with HCV or HBV. The HIV/HCV coinfection is more common in individuals who have a history of drug addiction. The aims of this study were to assess the HCV and HBV prevalence in HIV-infected patients and analyze their characteristics. Methods We considered the new HIV diagnoses notified by the regional surveillance system of Tuscany from 2009 to 2013. Descriptive analyses were conducted on the socio-demographic characteristics, routes of transmission, and reason to perform the test. In coinfected patients we assessed the risk for being late presenter (LP) or the risk of having AIDS. Results In 5 years of surveillance a total of 1354 new HIV diagnoses were notified: 1188 (87.7%) were HIV alone, 106 (7.8%) HIV/HCV, 56 (4.1%) HIV/HBV, and 4 (0.33%) HIV/HCV/HBV. The main risk factor was injection drug use in 52.8% of HCV/HIV cases, while in HIV/HBV patients the main risk factor was sexual exposure. HIV/HBV coinfected patients showed worse clinical and immunological features than HIV and HIV/HCV patients: 78.6% had CD4 count less than 350 mm−3 (vs. 54.6% and 62.1%, respectively) and 39.4% had AIDS (vs 20.7% and 7.6%). The risk for being LP triples for HIV/HBV (OR 2.98; 95% IC: 1.56–5.70) than patients with HIV alone. Conclusions We have observed less advanced disease in HIV and HCV-HIV patients compared with HBV–HIV coinfected patients. Moreover, our results show a higher prevalence of HIV/HCV among drug addicts and in the age-group 35–59, corresponding to those born in years considered most at risk for addiction. This study also confirms the finding of a less advanced HIV disease in HIV/HCV coinfected patients.